Evaluation of Human Capital: Approaches and Solutions (UNWE Yearbook, 2014)
The present study is dedicated to some basic approaches and solutions for the evaluation of human capital. The study presents the characteristic features of human capital and the main investors in this capital – individuals, business and state. The main methodological approaches for evaluating human capital are summarized and special attention is given to their advantages and disadvantages. Using the approach of Mulligan and Sala-I-Martin and the rich primary database for Bulgaria were carried out specific evaluations of the human capital on basic territorial units and economic activities.Major role in the study is given to the approaches to evaluate the return on investment in human capital. On this basis, a number of evaluations for return on investments in education are presented as well as to the profitability of an education year and a year of potential professional experience in Bulgaria.The research tools and information base in Bulgaria create the opportunity to be carried out further researches on human capital and return on investment.